Study of Electronic and Magnetic Properties of CuPd, CuPt, Cu3Pd and Cu3Pt: Tight Binding Linear Muffin-Tin Orbitals Approach - Dahal, Shiva; Kafle, Gyanu; Kaphle, Gopi Chandra; Adhikari, Narayan Prasad (Journal of Institute of Science and Technology, 2015)
Electronic structure of ordered alloys CuPd, CuPt, Cu3Pd and Cu3Pt have been studied using Tight Binding Linear Muffin-Tin Orbitals Atomic Sphere Approximation (TB-LMTO-ASA). For the electronic properties, we have performed band structure calculations. Our findings show that all the systems considered are metallic in nature. To know the contribution of the orbitals in the bands, the system is analyzed via fat bands which reveal most of the contributions on valence band for CuPd, CuPt, Cu3Pd and Cu3Pt is from d-orbital and on conduction band is from s and p-orbitals. We have also checked the magnetic properties of the alloys. The density of states for spin up and spin down electrons have found to be same in each and every steps, showing non-magnetic nature of CuPd, CuPt, Cu3Pd and Cu3Pt. Journal of Institute of Science and Technology, 2014, 19(1): 137-144